The art of digital audio - Watkinson, John 1950- (Focal Press, 2001)
This book is described as "the most comprehensive book on digital audio to date", and is widely acclaimed as an industry "bible". Covering the very latest developments in digital audio technology, it provides a thorough introduction to the theory as well as acting as an authoritative and comprehensive professional reference source. Everything you need is here from the fundamental principles to the latest applications, written in an award-winning style with clear explanations from first principles. New material covered includes internet audio, PC audio technology, DVD, MPEG audio compression, digital audio broadcasting and audio networks. Whether you are in the field of audio engineering, sound recording, music technology, broadcasting and communications media or audio design and installation, this book has it all. Written by a leading international audio specialist, who conducts professional seminars and workshops around the world, the book has been road tested for many years by professional seminar attendees and students to ensure their needs are taken into account, and all the right information is covered.; Digital audio professionals will find everything they need here, from the fundamental principles to the latest applications, written in an award-winning style with clear explanations from first principles. John Watkinson is an international consultant in audio, video and data recording. He is a Fellow of the AES, a member of the British Computer Society and a chartered information systems practitioner. He presents lectures, seminars, conference papers and training courses worldwide. He is the author of many other Focal Press books, including: the Kraszna-Krausz award winning "MPEG-2"; "The Art of Digital Audio"; "An Introduction to Digital Video"; "The Art of Sound Reproduction"; "An Introduction to Digital Audio"; and, "TV Fundamentals and Audio for Television". He is also co-author, with Francis Rumsey, of "The Digital Interface Handbook", and contributor to the "Loudspeaker and Headphone Handbook, 3rd edition."
Includes bibliographical references and index. - Print version record
Keywords: Sound -- Recording and reproducing -- Digital techniques; TECHNOLOGY & ENGINEERING; Electrical; Sound; Recording and reproducing; Digital techniques